Excited state in nanofluid containing perovskite manganate particles - Tuan, Vu Anh; Tho, Nguyen Duc; Yen, Pham Duc Huyen; Thanh, Phung Quoc; Nhat, Hoang Nam (VNU Journal of Science: Mathematics - Physics; Vol 29 No 2, 2013)
Abstract : The nanofluids containing the surface activated particles have great application potential in modern technology. In this paper, we studied the optical properties of the ceramic particles of forms Ca(FeMn)O 3 and (CaPr)(MnRu)O 3 dispersed in water solution by using SPAN-80 as surface activated agent (called surfactant). The UV-Vis absorption and photoluminescence spectroscopies were involved. The results showed that the prepared nanofluids possess the different optical properties in comparision with their crystalline counterparts. In facts, they showed clear blue shifts of spectral lines, changes of band gap, and especially enhancements of emission intensities. Keywords: Perovskite; Manganate; Structure; Electronic.